Green HRM and green competitive advantage in hotel and tourism industry: a mediated moderation model using eco-innovation and green psychological climate - Alshehri, Nawaf Zarie; Baquero, Asier; Abd-Elhady, Mohamed Hani; Salama, Wagih M. E.; Khairy, Hazem Ahmed; Abouelenien, Rania Elsayed Ibrahim (GeoJournal of Tourism and Geosites, 2024)
This study investigates the impact of green HRM (GHRM) on green competitive advantage (GCA), examining the mediating role of eco-innovation and the moderating role of green psychological climate (GPC). The study surveyed 472 fulltime employees in five-star hotels and travel agencies, developing and testing a five-hypothesis research model using PLS-SEM. Results revealed that GHRM positively impacts GCA and eco-innovation. Eco-innovation positively impacts GCA. In addition, GPC has a positive moderating influence on the relationship between GHRM and eco-innovation. Furthermore, Eco-innovation significantly mediates the relationship between GHRM and GCA.
Keywords: green HRM; green competitive advantage; eco-innovation; green psychological climate; hotel and tourism industry